Implementation of 3D AR Learning Media to Increase Learning Interest in Computational Thinking Materials: A Case Study of the Informatics Subject at a Public Junior High School in Pademawu, Madura, Indonesia - Minarto, Agus; Muhajir; Hatip, Ahmad (The Indonesian Institute of Science and Technology Research, 2025)
The use of technology-based learning media has become a necessity in the world of modern education. As a technological innovation, 3D Augmented Reality (AR) offers an immersive and interactive learning experience. This study aims to describe the implementation of 3D AR-based learning media in increasing student interest in Information and Communication Technology (ICT) subjects, especially the material of computational thinking at SMP Negeri 2 Pademawu, Madura, Indonesia. This research uses a qualitative approach with descriptive methods. Data were collected through observation, interviews, and documentation of teachers and students in the 8th grade. The results showed that using 3D AR media increased student engagement during the learning process, helped visualize the concept of computational thinking, and generated enthusiasm in completing creative tasks. 3D AR media can make theoretical ICT learning more concrete, engaging, and meaningful.